Principles of agribusiness management - Beierlein, James G. (Prentice-Hall, 1986)
A comprehensive, straightforward presentation, the substantially revised Third Edition places the evolving agri-food system in a global perspective. The authors present topics in a logical sequence built around the four functions of management--planning, organizing, controlling, and directing. Everything a manager does is related to efficiently, effectively maximizing long-term profits by profitably satisfying customers' needs. This unifying theme makes it easier for readers to build, relate, and integrate all the material presented. The authors' practical experience and their many years as educators combine to maximize learning. They employ the best teaching and learning practices in a readable, jargon-free style. A step-by-step approach with many worked examples emphasizes the application of basic, practical business management skills in marketing, demand analysis, forecasting, production, finance, leadership, and human resource management. Cases engage readers' minds by promoting active and collaborative learning. Each well-organized chapter includes a list of learning objectives, highlights of the topics presented, and a chapter quiz.